2020
DOI: 10.1111/pbi.13437
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the phenotypic components and genetic architecture of maize stem vascular bundles using high‐throughput phenotypic analysis

Abstract: High-throughput phenotyping is increasingly becoming an important tool for rapid advancement of genetic gain in breeding programmes. Manual phenotyping of vascular bundles is tedious and time-consuming, which lags behind the rapid development of functional genomics in maize. More robust and automated techniques of phenotyping vascular bundles traits at highthroughput are urgently needed for large crop populations. In this study, we developed a standard process for stem micro-CT data acquisition and an automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 77 publications
2
30
0
Order By: Relevance
“…This maintenance of the value for heritability for most of the chemical traits goes along with the fact that biochemical traits responded similarly each year. Under I scenario, heritability of histological trait is in accordance with what is reported (rind thickness h 2 = 58% in Mazaheri et al, 2019; bundle-related traits h 2 from 12.8 to 83.6% in Zhang et al, 2020). However, histological traits were only impacted by NI scenario in 2014 but not in 2015 (see Figure 1 and section "Discussion").…”
Section: Distinct Qtl Mapped For Biochemical and Histological Traitssupporting
confidence: 87%
See 2 more Smart Citations
“…This maintenance of the value for heritability for most of the chemical traits goes along with the fact that biochemical traits responded similarly each year. Under I scenario, heritability of histological trait is in accordance with what is reported (rind thickness h 2 = 58% in Mazaheri et al, 2019; bundle-related traits h 2 from 12.8 to 83.6% in Zhang et al, 2020). However, histological traits were only impacted by NI scenario in 2014 but not in 2015 (see Figure 1 and section "Discussion").…”
Section: Distinct Qtl Mapped For Biochemical and Histological Traitssupporting
confidence: 87%
“…These authors also detected QTL for PCAest at the top of chromosome 2 and on chromosome 4, positions that colocalize with QTL for PCAest mapped in our study. The 1-Hist cluster did not colocalize with any association found by Zhang et al (2020) using a panel of 482 lines and computed tomography (Du et al, 2016). Nevertheless, the QTL for Bundle_number on chromosome 1 at 61.4 Mb colocalized with some of their associations.…”
Section: Distinct Qtl Mapped For Biochemical and Histological Traitsmentioning
confidence: 77%
See 1 more Smart Citation
“…A significant inverse correlation was observed between the vascular bundle size and density. Heckwolf et al (2015) and Zhang et al (2021) also found variations in stem diameter as well as in the area of the rind and pith of the inbred lines they analysed. Zhang et al (2021) further analysed the variation in vascular bundle traits and reported wide phenotypic variations in vascular bundle size, number, and distribution density.…”
Section: Discussionmentioning
confidence: 83%
“…Once tissues are segmented, it is a straightforward process to measure the rind thickness, pith area, vascular bundle area or vascular bundle size or shape. These descriptors were related to stem lodging ( Zhang et al, 2018 ), developmental stages ( Zhang et al, 2020 ), and water stress ( Legland et al, 2017 ; El Hage et al, 2018 ) or used to analyse the phenotypic variation between lines ( El Hage et al, 2018 ; Zhang et al, 2021 ). In addition to tissue segmentation, Devaux and Legland (2014) proposed applying grey-level granulometry using morphological closings to directly extract cell size distributions from grey-level images.…”
Section: Introductionmentioning
confidence: 99%